Gene signature driving invasive mucinous adenocarcinoma of the lung. Issue 4 (2nd March 2017) - Guo, Minzhe; Tomoshige, Koichi; Meister, Michael; Muley, Thomas; Fukazawa, Takuya; Tsuchiya, Tomoshi; Karns, Rebekah; Warth, Arne; Fink‐Baldauf, Iris M; Nagayasu, Takeshi; Naomoto, Yoshio; Xu, Yan; et al.
Abstract: Though invasive mucinous adenocarcinoma of the lung (IMA) is pathologically distinctive, the molecular mechanism driving IMA is not well understood, which hampers efforts to identify therapeutic targets. Here, by analyzing gene expression profiles of human and mouse IMA, we identified a Mucinous Lung Tumor Signature of 143 genes, which was unexpectedly enriched in mucin‐producing gastrointestinal, pancreatic, and breast cancers. The signature genes included transcription factors FOXA3, SPDEF, HNF4A, mucins MUC5AC, MUC5B, MUC3, and an inhibitory immune checkpoint VTCN1 / B7‐H4 (but not PD‐L1 / B7‐H1 ). Importantly, induction of FOXA3 or SPDEF along with mutant KRAS in lung epithelium was sufficient to develop benign or malignant mucinous lung tumors, respectively, in transgenic mice. FOXA3 and SPDEF induced MUC5AC and MUC5B, while HNF4A induced MUC3 in human mucinous lung cancer cells harboring a KRAS mutation. ChIP‐seq combined with CRISPR/Cas9 determined that upstream enhancer regions of the mucin genes MUC5AC and MUC5B, which were bound by SPDEF, were required for the expression of the mucin genes. Here, we report the molecular signature and gene regulatory network driving mucinous lung tumors. Synopsis: Invasive mucinous adenocarcinoma of the lung (IMA) is now defined not only pathologically but also at the molecular level. A novel gene IMA signature characterizes human IMA cases that bear KRAS mutations. The immune checkpoint VTCN1/B7‐H4 but not PD‐L1/B7‐H1 correlates with mucinous markers. The anti‐mucous transcription factor NKX2‐1 induces PD‐L1/B7‐H1 and suppresses the pro‐mucous transcription factors FOXA3, SPDEF, and HNF4A. Distal enhancers bound by SPDEF are required for the expression of MUC5AC and MUC5B. Abstract : Invasive mucinous adenocarcinoma of the lung (IMA) is now defined not only pathologically but also at the molecular level.